The relationship between socio - cultural factors and sport participation in schools : a case study of Germiston High School in the Gauteng Province - Rakgole, Molatelo Walter (University of Limpopo, 2018)
The post-apartheid socio-cultural, economic and political dispensation in South Africa have prompted a high-level perceived potential inclusion in sport-participating in different aspect of self-development regardless of culture, economic and social difference across the nation. However, little is understood, from an empirical viewpoint, about the potential challenges and limits towards the successful participation in sport in South Africa. The purpose of this study was to investigate the relationship between socio-cultural factors and sport participation at Germiston High School in the Gauteng Province. A quantitative research was conducted using case study research design method. A Non-probability sampling method was done through purposive sampling method to select Grade 8 to Grade 12 students from. Data collection was done using self-administered questionnaires. There were one hundred and forty-seven students that participated in a survey of self-administered questionnaires at Germiston High School. The findings of the study reveal that sport-participation is highly linked to socio-cultural and economic aspects among students. For students, teachers are expected to be involved in sport-participation and be of the forefront of inclusiveness. It also was found that sport preference among students is linked to their important others. Thus, a full experience of sport-participation through resources available at school is compromised for many students. Schools, the Ministry of Education, Sports and Culture together with sponsors and parents are encouraged to intervene in promoting sport participation.
Thesis (M. Dev.) -- University of Limpopo, 2018
Keywords: Socio - culture; Sports participation; Post apartheid; Economic development; Economic development - Cross-cultural studies.